The effect of Trichoderma on the growth and development of tomato and bean under greenhouse and field conditions - Ban, Gwendolyn; Akanda, Shamsul; Maino, Macquin (Annals of Tropical Research, 2018)
Trichoderma’s plant growth stimulating effect is well-recognized besides its well-known role as a biocontrol agent against plant diseases. Two greenhouse and field studies were conducted at the Papua New Guinea University of Technology (PNGUOT) to test the effects of Trichoderma harzianum on the growth of tomato and bean plants. Greenhouse potted plants were inoculated with three T. harzianum strains at 106 CFUmL-1, whereas, the field experiments were inoculated with T. harzianum strain LIPIMCO548 in rice bran at 0, 25, 50 and 75g/m2 soil. In the greenhouse experiments, Trichoderma inoculation increased the root and shoot length, and total fresh weight of bean plant up to 16.57, 20.79 and 21.37%, respectively over the un-inoculated control. For tomato plants, significantly higher (p ≤0.05, LSD) average root growth was observed when inoculated with T. harzianum strain CE262 over the control. On average, Trichoderma inoculation increased the root and shoot length, and the fresh weight up to 26.4, 9.6 and 18.8%, respectively over the control. Similar growth patterns were also observed in the field experiments. These results will be of immense value to vegetable growers in Papua New Guinea (PNG), especially to the intensive vegetable growing areas in the highland regions of the country.